Securing Financial Systems with Block chain: A Comprehensive Review of Block chain and Cybersecurity Practices - Abid, Noman (International Journal of Multidisciplinary Sciences and Arts, 2024)
New and innovative block chain technology is becoming the key in enhancing the security, transparency and efficiency in the financial sector. However, as financial applications based on the block chain expand and improve, so do the block chain threats and safety concerns. This paper aims to discuss the aspects of the block chain security with reference to the financial system and its advantages and drawbacks. It embraces major risks like 51% attacks, smart contract exploits, phishing, and data privacy and security issues; new risks from quantum computing and Decentralized finance (DeFi) platforms. Best practices also outlined in the paper include the use of an industry-grade cryptographic algorithm, a robust multi-signature authentication technique, auditing of the block chain application at regular intervals, the adoption of secure, decentralized identity verification and management, as well as compliance with industry standards such as KYC and AML. It also underlines the need to establish effective access controls and to develop capability in scaling solutions and sustained monitoring. Lastly, it can be noted that the acquisition of block chain-based financial applications entails the use of a combination of measures to address existing and future risks. As these best practices are implemented and the threats advance, the financial institutions will be better placed to realize the full value of block chain technology while at the same time protecting the privacy and security of people’s financial transactions.